On the volumes of deep carbon — the initial donor of hydrocarbons on the Earth - Timursiev, A.I. (Geofizicheskiy Zhurnal, 2021)
Existing notions on the distribution of carbon on the Earth have been considered in the article. By the example of the data on carbon content in the upper mantle of the Earth obtained in the west of the USA by deep seismic tomography method the appraisal of the resource potential of the interior has been made within the limits of the theory of the deep abiogenous-mantle origin of oil and gas. According to the given appraisal, the partly melted zone (reservoir) contains not less than 1.2·1017 kg of volatiles (Q, kg), such as H or C. Calculation by carbon (С) taking into account the initial data demonstrated that the weight content (concentration) of carbon per unit volume of the Earth crust and upper mantle for which the appraisals of carbon content were completed will be 1 333.3 kg/m3 or 1.3 t/m3 (1.3 g/cm3). With average amount of melt of the rocks of the upper mantle 0.5±0.2 % (per volume), the volume of the area of melting of the Earth crust (deep carbon reservoir), containing the appraised volume of volatiles, will be: 4.5·1011 m3. In such a notion the weight content (concentration) of carbon per unit volume of partly melted zone of deep carbon reservoir will be: 2.67·105 kg/m3 or 266.67 t/m3 (266.67 g/cm3). These are very high figures if not to say fantastically high, characterizing not only high content of carbon and hydrogen as the main donors of hydrocarbons but also characterizing concentration of these elements within definite zones of the upper mantle of the Earth (asthenospheric layer) by all components (composition, concentration, phase state, PT-conditions), which is referred by our opinion to the sources of deep oil and gas formation. The data presented allow us to affirm that the problem of donors of HC of deep, abiogenous-mantle genesis has been resolved in our concept, and the source has been determined with high probability of the primary donors of HC in the section of the mantle and iron-carbon core of the Earth having inexhaustible resources of primary carbon, with its phase composition depending on PT conditions of the terrestrial envelopes might be crystalline (diamond phase, iron and nickel compounds (Fen+Nin)+Cn, iron carbides, for example — FeC, Fe2C, Fe3C (cementite) et al.), liquid (for example, the melt with admixture of sulfur and other volatiles H-N-F-O-Cl) and gaseous (СО2 gaseous only in the mantle, higher than D″ layer). In this case HC synthesis in industrial volumes is realized in the process of hydrogenation of deep carbon on the ascending hydrogen streams within the limits of asthenospheric lenses favoured by the presence of reaction volume here, catalysts and the necessary PT-conditions for polymerization of hydrocarbon radicals.